KETENTUAN HUKUM MEMPERJUALBELIKAN KOPI LUWAK - Pani Akhiruddin Siregar; Wastka Ningrum; Suryani Suryani (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2023)
AbstractCivet coffee is safe to consume. Although the coffee beans come out in the process through the civet anus in the form of feces. Keep the coffee intact. Qualitative research methods with a normative legal approach. In fact, normative legal research to examine law is conceptualized as a rule that applies in society and is the basis for one's behavior, such as legal provisions for buying and selling civet coffee. Therefore, this research aims to examine the legal provisions for buying and selling civet coffee â€œpermissibleâ€ based on: (1) Fatwa Decree of the MUI Fatwa Commission Number 07 of 2010 which concerning Fatwa on Civet Coffee; and (2) Fatwa MPU Aceh Number 07 of 2011 which concerning Fatwa on Civet Coffee Law. The results of the research that the legal provisions for buying and selling civet coffee based on: (1) Fatwa Decree of the MUI Fatwa Commission Number 07 of 2010 which concerning Fatwa on Civet Coffee; and (2) Fatwa MPU Aceh Number 07 of 2011 which concerning Fatwa on Civet Coffee Law.Keywords: Civet Coffee; Coffee Beans; Mutanajjis; Selling; Halal Civet Coffee.